THE IMPORTANCE OF FREE ECONOMIC ZONES IN A MARKET ECONOMY - Ro‘zibayeva Nargiza Hakimovna; Narzullayev Jasurbek Toshbo‘ri o‘g‘li (Scholars Digest Publishing, 2023)
The article is devoted to the study of the importance of free economic zones (FEZ) in a modern market economy. We analyze the effectiveness and impact of FEZs on economic development, drawing on examples of successful and unsuccessful implementations of such zones. Particular attention is paid to the role of FEZs in attracting foreign investment, stimulating innovation, creating jobs, and ensuring economic diversification. The article also examines the challenges faced by FEZs and offers recommendations for optimizing their performance in today's dynamic economic environment.
Keywords: Free economic zones (FEZ), foreign investment, economic diversification, innovation, jobs, economic development, globalization, economic growth, FEZ efficiency, market economy.